Geo-blocking of Non Audio-visual Digital Media Content in the EU Digital Single Market - Georgios Alaveras; Estrella Gomez-Herrera; Bertin Martens (European Commission, Joint Research Centre (JRC), 2017)
This study measures the extent of cross-border geo-blocking and the impact on product availability and pricing for three non-audio-visual digital media products (music, e-books and games) in the EU Digital Single Market. We find that cross-border access to online media stores is generally blocked for the products and distributors surveyed in this study, though it can usually be circumvented. By contrast, cross-border availability is high, reaching around 98.6% for e-books on Amazon, 90% for downloadable music on iTunes, and 81.1% and 90.5% respectively for PS3 and PS4 PlayStation games. We could not directly verify cross-border availability of music in streaming services but a small sample test suggests that it could reach around 96% on Spotify. We find that the frequency of cross-country price differentiation is limited for games in the Sony PlayStation stores (less than 4%) but higher for downloadable music in the Apple iTunes stores (11.5%) and Amazon e-book stores (26%). Much of this price differentiation is driven by exchange rates and rounding off prices in country stores not denominated in Euro. In music, price discrimination is used mostly to extract higher prices from high-income consumers and for more popular songs with a lower price elasticity of demand. Subscription prices for main music streaming services are strongly correlated with country per capita income levels. Geographical market differentiation and geo-blocking in digital media is often attributed to the territoriality of the copyright management regime. In most cases rights holders are in a position to issue multi-territorial licenses. For commercial reasons however they may prefer to exercise their rights on a territorial basis. The welfare effect of geo-blocking on sellers can be safely assumed to be positive otherwise sellers would not apply this commercial strategy. The impact on consumer welfare is a-priori ambiguous. Geo-blocking reduces the extent of product variety available to consumers. Whether it increases or reduces consumer welfare is an empirical question. The data required to empirically estimate the impact of (lifting) geo-blocking restrictions on welfare are held by the private platform operators. A future assessment can only be made if the required data on product prices and sales are made available to independent researchers. Lifting geo-blocking restrictions will induce price arbitrage between country markets. That may put pressure on sellers to reduce price differentiation and push some prices up, others down. The price response of sellers is hard to predict and may have repercussions not only on downstream consumers but also on upstream parts of the supply chain. Price convergence is unlikely to be perfect and some differentiation may continue to exist because trade costs between country stores may not fall to zero (exchange rates, means of payment, linguistic trade barriers, etc.).
Keywords: D23; K11; 330; digital single market; copyright; digital media; audio-visual; music; e-books; online games